The RelationsThe Relationship between Lifestyle with the Risk of Diabetes Mellitus in Staff and Lecturers of Universitas Megarezky - Irwansyah, Irwansyah; Kasim, Ilcham Syarief; Bohari, Bohari (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: An unhealthy lifestyle can lead to high cases of diabetes mellitus, especially in adults and adolescents. AIM: This study aims to determine the relationship between lifestyle and the risk of diabetes mellitus. METHODS: This research is a cross-sectional study. The population in this study was 198 with a sample of 91 respondents, obtained using purposive sampling technique. RESULTS: There were 50 (55%) respondents who had a good lifestyle and 41 (45%) had a poor lifestyle. There were 53 (58%) respondents who are at risk for diabetes mellitus, 38 (42%) respondents were not at risk, and there is the relationship between lifestyle with diabetes risk with p = 0.00. CONCLUSION: Staff and lecturers Universitas Megarezky have a higher risk of developing diabetes mellitus. An unhealthy lifestyle is a risk factor for diabetes mellitus in staff and lecturers at Universitas Megarezky.